Click Chemistry on Solid Phase: Parallel Synthesis of N-Benzyltriazole Carboxamides as Super-Potent G-Protein Coupled Receptor Ligands - Löber, Stefan; Gmeiner, Peter; Hübner, Harald; et al. (Journal of Combinatorial Chemistry, 2006)
The click chemistry-based backbone amide linker 1 was employed for an efficient and practical parallel synthesis of 1,2,3-triazole carboxamides when 1,3-dipolar cycloaddition was exploited for both the construction of a compound library and the functionalization of the resin. A three-step solid-phase-supported sequence included reductive animation by N-phenylpiperazinyl-substituted alkylamines, N-acylation by alkynoic acids, and azide-alkyne [3 + 2] cycloaddition. In most cases, cleavage under acidic conditions yielded the final products in excellent purities. A focused library of 60 target compounds was screened for G-protein coupled receptor binding employing eight biogenic amine receptors. Radioligand displacement experiments indicated a number of hit compounds revealing excellent receptor recognition when the methyl-substituted N-benzyltriazoles 29, 40, and 42 exhibited superior affinities for the α1 subtype (Ki = 0.056-0.058 nM). © 2006 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.lphch.clickc